Ntrk1 mutation co-segregating with bipolar disorder and inherited kidney disease in a multiplex family causes defects in neuronal growth and depression-like behavior in mice - Nakajima, Kazuo; Miranda, Alannah; Craig, David W; Shekhtman, Tatyana; Kmoch, Stanislav; Bleyer, Anthony; Szelinger, Szabolcs; Kato, Tadafumi; Kelsoe, John R (Translational psychiatry, 2020)
Previously, we reported a family in which bipolar disorder (BD) co-segregates with a Mendelian kidney disorder linked to 1q22. The causative renal gene was later identified as MUC1. Genome-wide linkage analysis of BD in the family yielded a peak at 1q22 that encompassed the NTRK1 and MUC1 genes. NTRK1 codes for TrkA (Tropomyosin-related kinase A) which is essential for development of the cholinergic nervous system. Whole genome sequencing of the proband identified a damaging missense mutation, E492K, in NTRK1. Induced pluripotent stem cells were generated from family members, and then differentiated to neural stem cells (NSCs). E492K NSCs had reduced neurite outgrowth. A conditional knock-in mouse line, harboring the point mutation in the brain, showed depression-like behavior in the tail suspension test following challenge by physostigmine, a cholinesterase inhibitor. These results are consistent with the cholinergic hypothesis of depression. They imply that the NTRK1 E492K mutation, impairs cholinergic neurotransmission, and may convey susceptibility to bipolar disorder.
Keywords: bipolární porucha; Depression; myši; receptor trkA; mutace; Kidney Diseases; deprese; zvířata; Mice; Mutation; nemoci ledvin; Receptor, trkA; Bipolar Disorder; Animals